Crustal versus mantle origin of carbonate xenoliths from Kimberley region kimberlites using C-O-Sr-Nd-Pb isotopes and trace element abundances. (1st December 2019) - Howarth, Geoffrey H.; Moore, Andy E.; Harris, Chris; van der Meer, Quinten H.A.; le Roux, Petrus
Abstract: Carbonate-bearing assemblages in the mantle have been interpreted to be the source for Si-undersaturated, CO2 -rich magmas, including kimberlites. However, direct evidence for carbonate in the mantle is rare in the contemporary literature. Here we present petrography, trace element, and C-O-Sr-Nd-Pb isotope composition for a suite of carbonate xenoliths from the Kimberley region kimberlites to ascertain their mantle or crustal origin and gain insight to the potential for the occurrence of carbonate in the mantle. Carbonate xenoliths were found in large kimberlite blocks from the Bultfontein kimberlite and Big Hole region. The xenoliths are characterised by pale green alteration margins made of fine-grained microlites of an unknown mineral as well as spherules surrounded by glassy material. They are generally 1–4 cm in size, coarse-grained (1–2 mm), and comprised entirely of calcite. Carbonate xenoliths from the Bultfontein kimberlite have low total REE concentrations (0.2–4.9 ppm), constant 87 Sr/ 86 Sri (0.7047–0.7049) combined with variable ƐNdi (−0.1 to −26.2) and 206 Pb/ 204 Pbi, 207 Pb/ 204 Pbi, and 208 Pb/ 204 Pbi of 16.7–18.8, 15.3–15.6, 36.5–38.4, respectively. Xenoliths from the Big Hole sample have higher 87 Sr/ 86 Sri (0.7088–0.7095), lower ƐNdi (−24.5 to −3.8), and 206 Pb/ 204 Pbi, 207 Pb/ 204 Pbi, and 208 Pb/ 204 Pbi of 18.9–19.9, 15.7–15.8, 38.4–38.8, respectively. The δ 13 C values for both Bultfontein (−5.7 to −6.6‰) and Big Hole (−4.7 to −5.4‰) carbonates are within the typical range expected for mantle-derived carbonate. The δ 18 O values (15.5–17.5‰) are higher than those of mantle silicate rocks, indicative of late-stage low-temperature interaction with fluids; a common feature of groundmass calcite in the Kimberley kimberlites. The Sr- and C- isotope composition of the Bultfontein xenoliths indicates a mantle origin whereas the Big Hole xenolith Sr- and C-isotopes are more ambiguous. Isotope mixing models are inconsistent with interaction between the host kimberlite and carbonate xenoliths. Correlation between ƐNdi and δ 18 O values for the Bultfontein xenoliths indicates late-stage interaction with low-temperature fluids, which may also be responsible for the large range in ƐNdi. This in turn indicates that the highest ƐNdi of −0.1 represents the primary carbonate xenolith signature, and this value overlaps typical Group I kimberlites. We discuss two possible origins for the carbonate xenoliths. (1) Carbonate xenoliths from the sub-continental lithospheric mantle (SCLM), where quenched margins and the large range of ƐNdi are related to formation in the mantle. (2) Carbonate xenoliths from an earlier phase of carbonatite magmatism. The similarity of isotope signatures of the Bultfontein carbonates to Group I kimberlite may further suggest a link between kimberlite and carbonatite volcanism such as observed elsewhere in the world.